The first zoeal stage morphology of Crossotonotus spinipes (De Man, 1888) and Pseudopalicus serripes (Alcock & Anderson, 1895), with implications for palicoid systematics (Crustacea: Brachyura: Palicoidea) - Clark, Paul F.; Fujita, Yoshihisa; Ball, Alexander D.; Ng, Peter K. L. (Zootaxa, 2012)
Traditionally, Crossotonotus spinipes (De Man, 1888) and Pseudopalicus serripes (Alcock & Anderson, 1895) were as-signed to the Crossotonotinae Moosa & Serène, 1981, and Palicinae Bouvier, 1898, respectively. However, Ng et al.(2008: 127) listed a number of major adult characters that suggested both subfamilies should be recognised as distinct fam-ilies within the Palicoidea Bouvier, 1898 (see also Castro 2010, 2011; Guinot et al. in prep.). Recently, ovigerous speci-mens of C. spinipes and P. serripes were collected from Okinawajima and Kumejima, central Ryukyu Islands, Japan. Thefirst zoeal stages of both species were hatched in the laboratory, dissected, examined, and the appendages illustrated anddescribed. Crossotonotus spinipes first stage zoeas were distinguished by three characters: the absence of lateral carapacespines (present in P. serripes), abdominal somite 4 with a pair of dorsolateral processes directed ventrally (absent in P.serripes) and the presence of a small lateral spine on the telson (absent in P. serripes). These distinguishing features appear to support the recent division of the Palicoidea into two families.